Vitrectomy for macular lesions in eyes with retinitis pigmentosa - Nowosielska, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Retinitis pigmentosa is a genetic disorder leading to severe visual impairment. So far, it is considered incurable. Furthermore, patients may suffer from additional complications, such us cataract, glaucoma and macular changes, causing further visual acuity and visual field deterioration. The aim of this paper is to present a case of retinitis pigmentosa in a patient treated with vitrectomy for macular hole in one eye and epiretinal membrane with pseudo macular hole in the other eye.